2014
DOI: 10.1039/c4cp02202e
|View full text |Cite
|
Sign up to set email alerts
|

Computational and ion mobility MS study of (all-S)-cyclohexylhemicucurbit[6]uril structure and complexes

Abstract: A computational study of (all-S)-cyclohexylhemicucurbit[6]uril and its complexes with anions (Cl(-), Br(-), I(-) and HCOO(-)), the proton (H(+)) and non-dissociated acid (HCl, HBr, HI and HCOOH) guests was performed. The geometries of guest-host complexes were optimized via density functional theory using the BP86 functional, SV(P) basis set and Stuttgart pseudopotentials for iodide. Binding affinities and their trends were evaluated at the BP86/TZVPD level of theory. In addition, the quantum theory of atoms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 64 publications
(122 reference statements)
0
35
0
Order By: Relevance
“…S2 and S3†). Halide anions (13 to 35 Å 3 in volume 36 ), while readily forming complexes with 6-membered hemicucurbiturils, 3741 appear to have very low affinity towards cycHC[8] , presumably due to a mismatch in size with the cavity of cycHC[8] . As expected, the affinity towards more heavily solvated anions was found to be lower than for weakly solvated ones.…”
Section: Resultsmentioning
confidence: 99%
“…S2 and S3†). Halide anions (13 to 35 Å 3 in volume 36 ), while readily forming complexes with 6-membered hemicucurbiturils, 3741 appear to have very low affinity towards cycHC[8] , presumably due to a mismatch in size with the cavity of cycHC[8] . As expected, the affinity towards more heavily solvated anions was found to be lower than for weakly solvated ones.…”
Section: Resultsmentioning
confidence: 99%
“…Gas phase calculationson on the (all-S)-cychmCB [6] indicated that the anions were located inside the cavity and the affinity of the anions (in gas phase) is Cl À > Br À > HCOO À > I À . [28] The existence of even larger macrocycles of cyclohexylhemicucurbit[n]uril (n = 7-10) were first shown in 2014 by analysing the reaction mixture of (all-R)-cychmCB [6] by HPLC-MS. [29] The (all-R)-cyclohexylhemicucurbit [8]uril (all-R-cychmCB [8]) was isolated in 11 % yield. The chloride and formate complexes of (all-R)-cychmCB [8] were detected in negativemode MS.…”
Section: Cyclohexylhemicucurbit[n]urilmentioning
confidence: 99%
“…Rapid equilibration between library members under controlled conditions is necessary, making imines, [16] hydrazones [17] (Scheme 2, A, B), disulphides [18] and boronates [19] currently the most applied linkers. [34] Computational and ionmobility MS study of cycHC [6] [35] in gas phase demonstrates that the favourable site for protonation of (S,S)-cycHC [6] was at a N-atom on the inside of the cavity (Figure 1, left side). the monomer and alkylthiourea is carried along as substituent of the resulting HC (Scheme 3, C).…”
Section: Dynamic Covalent Bondsmentioning
confidence: 99%
“…According to theoretical study in presence of water, the formation of the second CÀN bond and deprotonation is mediated by water and the urea C= O group (Scheme 3, A). [35] that the protonation site may depend on proton carrier and media. Therefore this dynamic multicomponent chemistry (Scheme 2 C) has been utilized in chiral sensing.…”
Section: Dynamic Covalent Bondsmentioning
confidence: 99%
See 1 more Smart Citation